Managing superteams: how team composition affect the team performance of public healthcare in Malaysia / Azlyn Ahmad Zawawi - Ahmad Zawawi, Azlyn (2021)
Public healthcare workers carry the responsibility of caring and healing for others. Their performance reflects the well-being of the end-receivers of their service, i.e., the patients. In the context of public healthcare, this means that the performance of the frontliners will ensure the well-being of the citizens, which will reflect the healthy growth of the nation. More often than not, healthcare workers work in a synergy and collaborative manner through team-working. High-performing teams are crucial in healthcare because this sector's tasks are highly interdependent, unpredictable, and dynamic (Bleakley, 2013). Healthcare teams are often faced with challenges that are complex and difficult to coordinate, requiring the teams to align high levels of collaboration between tasks, members' attributes, and the overall team strategy. Medical frontline workers are highly dependent on teams because high-performing teams will lead to a higher degree of members' satisfaction, decreased stress, increased quality of healthcare, reduced medical errors, and increased patient safety (Kalisch, Weaver, & Salas, 2009). The urge for healthcare workers to be coordinated in tasks signifies the importance of team performance in healthcare settings.